Lyrical Works of Elise Mercer: Toward a Typology of Poets of French Romanticism - V. I. Pinkovsky (Научный диалог)
As part of the development of the typology of the authors of French romanticism, the creative type represented by the French poetess Élisa Mercœur is determined (Élisa Mercœur, 1809—1835). The relevance of the work is due to the fact that the creation of a typology is a way both to streamline the studied material and to explore new, operating not with a disparate set of facts and subjective opinions, but with generalized conventional concepts. It is noted that the materials about Élisa Mercœur are currently in a state that requires such a typological design. As a result of the study, it was established that the poet, on the one hand, belongs to the category of writers whose biographies are mythologized in a romantic spirit. On the other hand, it is shown that she belongs to a rather numerous category of romantic writers who have creative abilities in the absence of a vivid originality and therefore are intended to popularize the achievements of outstanding authors, practically creating a “language of direction”, but nevertheless developing their own themes (mostly related to the privacy of authors). A typology of creative models of romantic lyrics is proposed in the article; one of the models that combines the authenticity of feelings and moderate complexity of the language of expression is the original work of Élisa Mercœur.